Introduction to English Syntax - Kreyer, Rolf; Mukherjee, Joybrato (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2010)
This book provides an overview of basic syntactic categories, analytical methods and theoretical frameworks that are needed for a comprehensive and systematic description and analysis of the syntax of English as it is spoken and written today. It is therefore useful for students of the English language but also for teachers who are looking for an overview of traditional syntactic analysis. In addition, the book explores various related aspects, such as syntactic variation, the relation between syntax and semantics, and psycholinguistic approaches to syntax. One focus throughout is to introduce the reader to the 'art' or science of syntactic argumentation. Almost all of the examples that are found in this book are drawn from language corpora - each syntactic concept, therefore, is exemplified by authentic language data- Resumé vydavatel
Keywords: angličtina; syntax; English language; elektronické knihy; učebnice; electronic books; textbooks